Analysis of the multicultural awareness level of guidance and counseling students at sriwijaya university - Rozzaqyah, Fadhlina; Alrefi, Alrefi; Rahmi, Rahmi; Sucipto, Sigit Dwi (Universitas Islam Negeri Raden Intan Lampung, 2023)
Indonesia is a country with people's backgrounds from various cultures, races, ethnicities, and beliefs. Cultural heritage by the community is applied to everyday life both in interacting with other people and in carrying out daily activities such as cultural rituals and beliefs which are the basis and guidelines for life that cannot be separated from individual development. Counseling teachers/counselors who work in communities with diverse cultures should have multicultural counseling competencies in terms of attitudes, knowledge, and skills. One of them is multicultural awareness to provide guidance and counseling services that are by the counselee's needs. The purpose of this research is to get a picture of the multicultural awareness of Guidance and Counseling students at Sriwijaya University. Respondents in this study amounted to 315 students. This study uses a descriptive quantitative method that analyzes the level of multicultural awareness and comparative techniques to compare between male and female students. The results showed that students had a moderate level of multicultural awareness, students very high, students moderate, students were in a low category, and students is very low. The results of the comparison study show that differences in multicultural awareness of female students are higher than that of male students.